2015
DOI: 10.1021/jp509415r
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Assisted Reactions toward Formation of Graphene Nanoribbons on Au(110) Surface

Abstract: Scanning tunneling microscopy and X-ray spectroscopy measurements are combined to first-principles simulations to investigate the formation of graphene nanoribbons (GNRs) on Au(110), as based on the surface-mediated reaction of 10,10′-dibromo-9,9′-bianthracene (DBBA) molecules. At variance with Au(111), two different pathways are identified for the GNR self-assembly on Au(110), as controlled by both the adsorption temperature and the surface coverage of the DBBA molecular precursors. Room-temperature DBBA depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
109
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(130 citation statements)
references
References 57 publications
21
109
0
Order By: Relevance
“…6,9 On the other hand, a bottom-up approach presuming on-surface reactions between molecular precursors was demonstrated to be a superior approach for production of atomically precise GNRs. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, armchair-edge GNRs with the width of 7 rows of C atoms (7-AGNRs) can be grown on certain metal substrates using DBBA molecule as a precursor.To date, this strategy was successfully implemented to prepare 7The growth mechanism leading to the formation of 7-AGNRs from DBBA on Au(111) and Cu(111) can be described in three steps: (i) surface-assisted dehalogenation of precursor molecules (in the case of Cu (111) followed by the formation of surface-stabilized structure); (ii) formation of linear polyanthracene chains via directional covalent C-C coupling of biradical molecular units and (iii) cyclodehydrogenation reaction upon further thermal activation.The on-surface polymerization reaction between halogen-substituted precursors, including stages (i) and (ii), is also known as Ullmann-type coupling reaction. 26,27 It has become an established route for tailored fabrication of covalent nanostructures in the last few years.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6,9 On the other hand, a bottom-up approach presuming on-surface reactions between molecular precursors was demonstrated to be a superior approach for production of atomically precise GNRs. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, armchair-edge GNRs with the width of 7 rows of C atoms (7-AGNRs) can be grown on certain metal substrates using DBBA molecule as a precursor.To date, this strategy was successfully implemented to prepare 7The growth mechanism leading to the formation of 7-AGNRs from DBBA on Au(111) and Cu(111) can be described in three steps: (i) surface-assisted dehalogenation of precursor molecules (in the case of Cu (111) followed by the formation of surface-stabilized structure); (ii) formation of linear polyanthracene chains via directional covalent C-C coupling of biradical molecular units and (iii) cyclodehydrogenation reaction upon further thermal activation.The on-surface polymerization reaction between halogen-substituted precursors, including stages (i) and (ii), is also known as Ullmann-type coupling reaction. 26,27 It has become an established route for tailored fabrication of covalent nanostructures in the last few years.…”
mentioning
confidence: 99%
“…Apart from the atomic structure of the molecular precursor itself it is essential to take into account substrate morphology and reactivity, in order to exert full control over the formation of molecular nanoarchitectures. 21,30,[35][36][37][38][39] The more reactive is the substrate, the more pronounced is its role in the bottom-up mechanism.The bottom-up growth of GNRs is not an exception. In our recent study 18 we have shown that on the reactive Cu(111) a complete dehalogenation of DBBA takes place at room temperature (RT) and is followed by the formation of polymer chains at temperatures around 100˚C, while for the less reactive Au(111) debromination of DBBA molecules occurs at around 200˚C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Br Br as cyclodehydrogenation reaction [85], lithography [16], and boronic acid polycondensation [54] were performed not long ago. Among them, the most typical one is the hierarchical polymerization that begins with the bottom-up synthetic Ullmann coupling and ends in cyclodehydrogenation reaction.…”
Section: Optimization Of Hierarchical Polymerizationmentioning
confidence: 99%
“…The self-assembly of functionalised molecules on surfaces is key for the development of novel 2D devices [1] for a variety of applications [2] including graphene and polymer formation [3][4][5], and semiconductor nanostructures [6,7]. Realisation of these applications requires the formation of highly-ordered self-assembled structures on surfaces.…”
Section: Introductionmentioning
confidence: 99%